2021
DOI: 10.9734/afsj/2021/v20i330283
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Enzymes and Germination Pattern: Upshot of High Salinity on Soluble Protein and Average Weight of Spinacia oleracea (Spinach) Seedlings

Abstract: Spinach (Spinacia oleracea L.) is widely considered as a functional food mainly due to its various beneficial components including vitamins, minerals, phytochemicals, bioactive and antioxidant compounds that stimulate health beyond basic nutrition. The overwhelming agricultural crop at salinity conditions faced several abiotic and biotic stresses that unfortunately reduced the potential applicability of highly nutritious plants. Therefore, in this study the response of antioxidant enzymes were studied at diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
2
0
1
Order By: Relevance
“…Low (0.02 mmol•L −1 ) melatonin significantly increased Pro concentration under high (200 mmol•L −1 ) NaCl treatment, while low and medium (0.1 mmol•L −1 ) melatonin decreased Pro concentration under low (50 mmol•L −1 ) NaCl treatment, approximating control levels. This concentrationdependent pattern aligns with previous research on SP concentration by Bano [52], and on SS concentration and Pro concentration by Cheng [53] in camphor pine. This may be due to melatonin's role as a signaling molecule influencing the synthesis of SP and SS [54], which is affected by NaCl stress concentration.…”
Section: Relationship Between Exogenous Melatonin and Osmoregulation ...supporting
confidence: 91%
“…Low (0.02 mmol•L −1 ) melatonin significantly increased Pro concentration under high (200 mmol•L −1 ) NaCl treatment, while low and medium (0.1 mmol•L −1 ) melatonin decreased Pro concentration under low (50 mmol•L −1 ) NaCl treatment, approximating control levels. This concentrationdependent pattern aligns with previous research on SP concentration by Bano [52], and on SS concentration and Pro concentration by Cheng [53] in camphor pine. This may be due to melatonin's role as a signaling molecule influencing the synthesis of SP and SS [54], which is affected by NaCl stress concentration.…”
Section: Relationship Between Exogenous Melatonin and Osmoregulation ...supporting
confidence: 91%
“…The total protein was higher at 50 and 150 mM NaCl and decreased at 200 mM NaCl (145.92,126.88,and 118.38 mg/g DW) respectively. This is in contrast to Bano et al (2021), who noticed an increase in the total protein under high saline conditions. However, the same results were documented in Kumar et al (2010) study, who noticed the rise of total protein content increased under saline stress, but this content decreased under high levels of salt, which agreed with our study.…”
Section: Discussioncontrasting
confidence: 94%
“…Gadallah (1999) explains that the reason behind the increment of soluble proteins is the degradation of some structural proteins. Also, Bano et al (2021) reported that soluble protein levels declined under saline conditions, especially at 800 mM, which is similar to our result.…”
Section: Discussionsupporting
confidence: 92%